Portraits of the Evaluation of Higher Education: The Cases of Brazil, Portugal and England (Global Journal of Human-Social Science, 2019)
The globalization of the idea and processes of evaluation of educational systems has made it possible among other discussions the emergence of the debate about the relation between the homogeneity of the abstractly universal models and the heterogeneity of the experiences with the evaluation in each national context Therefore this relationship is taken as the guiding principle of this article the scenarios of the evaluation of higher education in Brazil Portugal and England are here scopes for a comparative analysis with the central purpose of characterizing them on the one hand and situating them in the broader or global context of state and supranational regulation on the other The National System of Evaluation of Higher Education SINAES in Brazil the Portuguese Evaluation and Accreditation System coordinated by the Agency for Evaluation and Accreditation of Higher Education a private law foundation as well as the recent Teaching Excellence Framework TEF from the United Kingdom serve as corpus for this study
Keywords: evaluation; higher education; brazil; portugal; england; comparative analysis